Cross-metathesis of biorenewable dioxalates and diols to film-forming degradable polyoxalates - Rajput, Bhausaheb S.; Ram, Farsa; Menon, Shamal K.; Shanmuganathan, Kadhiravan; Chikkali, Samir H. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
Starting from commonly available sugar derivatives, a single step protocol to access a small family of isohexide-dioxalates (2a-c) has been established. The synthetic competence of 2a-c has been demonstrated by subjecting them to condensation polymerization. Quite surprisingly, the proton NMR of poly(isomannide-co-hexane)oxalate revealed a 1:2 ratio between isomannide-dioxalate (2a) and 1,6-hexanediol (3a) in the polymer backbone. This intriguing reactivity was found to be an outcome of a cross metathesis reaction between 2a and 3a. The cross metathesis products 3a[2-(2-methoxyacetoxy)ethyl 2-(2-hydroxyethoxy)-2-(3-oxydanylidene)acetate] and 2a(3R,6R)-6-hydroxyhexahydrofuro[3,2-b]-furan-3-yl methyl oxalate were isolated in a control experiment. Based on direct and indirect evidence, and control experiments, an alternative polymerization mechanism is proposed. Polymerization conditions were optimized to obtain polyoxalates P1(2a-3a)-P9(2c-3c) with molecular weights in the range of 14,000-68,000 g/mol, and narrow polydispersities. The identity of the polyoxalates was unambiguously established using 1-2D NMR spectroscopy, MALDI-ToF-MS, and GPC measurements. The practical implication of these polymers is demonstrated by preparing transparent, mechanically robust films. The environmental footprint of the selected polyoxalates was investigated by subjecting them to solution and solid-state degradation. The polyoxalates were found to be amenable to degradation. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1584-1592

Flexible composite mechanical energy harvester from a ferroelectric organoamino phosphonium salt - Vijayakanth, Thangavel; Srivastava, Anant Kumar; Ram, Farsa; Kulkarni, Priyangi; Shanmuganathan, Kadhiravan; Praveenkumar, Balu; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2018)
A new binary organic salt diphenyl diisopropylamino phosphonium hexaflurophosphate (DPDPPF6) was shown to exhibit a good ferroelectric response and employed for mechanical energy harvesting application. The phosphonium salt crystallizes in the monoclinic noncentrosymmetric space group Cc and exhibits an H-bonded 1D chain structure due to N-HF interactions. Ferroelectric measurements on the single crystals of DPDPPF6 gave a well-saturated rectangular hysteresis loop with a remnant (P-r) polarization value of 6Ccm(-2). Further, composite devices based on polydimethylsiloxane (PDMS) films for various weight percentages (3, 5, 7, 10 and 20wt%) of DPDPPF6 were prepared and examined for power generation by using an impact test setup. A maximum output peak-to-peak voltage (V-PP) of 8.5V and an output peak-to-peak current (I-PP) of 0.5A was obtained for the non-poled composite film with 10wt% of DPDPPF6. These results show the efficacy of organic ferroelectric substances as potential micropower generators.
Keywords: binary phosphonium salts; energy conversion; ferroelectricity; hydrogen bonding; polymer composites

Fluorinated nanocellulose-reinforced all-organic flexible ferroelectric nanocomposites for energy generation - Ram, Farsa; Ambone, Tushar; Sharma, Aakash; Murugesan, Rajarathinam; Kajale, Deepak; Borkar, Vivek; Ali, Shaikh Faruque; Balu, Praveen Kumar; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Journal of Physical Chemistry C, 2018)
We report here enhanced ferroelectric crystal formation and energy generation properties of polyvinylidene fluoride (PVDF) in the presence of surface-modified crystalline nanocellulose. Incorporation of only 2-5 wt % fluorinated nanocellulose (FNC) in PVDF has been found to significantly induce polar beta/gamma-phase crystallization as compared to the addition of unmodified nanocellulose (carboxylated nanocellulose). A device made up of electrically poled PVDF/FNC composite films yielded 2 orders of magnitude higher voltage output than neat PVDF in vibrational energy harvesting. This remarkable increase in energy generation properties of PVDF at such a low loading of an organic natural biopolymer could be attributed to the tailored surface chemistry of nanocellulose, facilitating strong interfacial interactions between PVDF and FNC. Interestingly, energy harvesting devices fabricated from PVDF/FNC nanocomposites charged a 4.7 mu F capacitor at significantly faster rate and the accumulated voltage on capacitor was 3.8 times greater than neat PVDF. The fact that PVDF/FNC nanocomposites still retain a strain at break of 10-15% and can charge a capacitor in few seconds suggests potential use of these nanocomposites as flexible energy harvesting materials at large strain conditions.

Functionalized carbon nanotube reinforced polymer nanocomposite microcapsules with enhanced stiffness - Jagtap, Siddheshwar B.; Patil, Vishal D.; Suresh, Karthika; Ram, Farsa; Mohan, Muthu Subramanian; Rajput, Shatruhan S.; Patil, Shivprasad; Shukla, Parshuram G.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2018)
Microcapsules with tunable mechanical properties are highly desirable in pressure sensitive applications. We report here a facile approach to prepare polyurea/multiwall carbon nanotube (MWCNTs) nanocomposite microcapsules (MICs) with enhanced stiffness. A model compound dimethyl phthalate (DMP) was used as core material. MWCNTs were modified with reactive functional groups namely carboxyl (-COOH), amines (-NH2), and isocyanates (-NCO) to ensure a stronger interface between polymer wall and MWCNTs. Functionalization of MWCNTs was corroborated by Fourier transformed infrared spectroscopy (FTIR). Scanning electron microscopy (SEM) was employed to study the surface morphology of MICs. The presence of MWCNTs in the microcapsule wall was confirmed by transmission electron microscopy (TEM). MICs with functionalized MWCNTs show almost 100% increase in stiffness with respect to pristine capsules. All MICs show 92-97 +/- 1% encapsulation efficiency. The approach used in this paper can be broadly utilized to tune the mechanical properties of the microcapsules.

Melanin-based composite materials for multifunctional applications - Shanmuganathan, Kadhiravan; Ram, Farsa; Pimpalkar, Nikhil (256th National Meeting and Exposition of the American-Chemical-Society (ACS) - Nanoscience, Nanotechnology and Beyond, 2018)
256th National Meeting and Exposition of the American-Chemical-Society (ACS) - Nanoscience, Nanotechnology and Beyond

All-organic composites of ferro- and piezoelectric phosphonium salts for mechanical energy harvesting application - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Chemistry of Materials, 2019)
Molecular ferroelectrics owing to their lightweight, flexibility, and phase stability are drawing attention in the fields of flexible electronics, optical devices, and energy materials. In this paper, we report a series of binary organoamino phosphonium salts containing triphenyl isopropylaminophosphonium (TPAP), diphenyl diisopropylaminophosphonium (DPDP), phenyl triisopropylaminophosphonium (PTAP), and tetraisopropylaminophosphonium (TIAP) cations supported by lower symmetric tetrahedral BF4-, ClO4-, and IO4- anions. The P-E hysteresis loop measurements on these polar organic salts gave high remnant polarization (P-r) values of 35.36, 21.83, and 21.12 mu C cm(-2) for the DPDP center dot BF4, DPDP center dot ClO4, and DPDP center dot IO4 salts, respectively, having 1D hydrogen-bonded chain structures built from strong N-H center dot center dot center dot X (X = F or 0) interactions. For the first time, highly flexible composite devices have been prepared for the piezoelectric salts TPAP center dot BF4, DPDP center dot BF4, and TIAR center dot BF4 using thermoplastic polyurethane (TPU) as the matrix. The observed maximum peak-to-peak output voltages (V-pp) for the 10 wt % composite devices of TPAP center dot BF4/TPU, DPDP center dot BF4/TPU, and TIAP center dot BF4/TPU are found to be 7.37, 8.95, and 4.75 V, respectively. These composite devices exhibit excellent durability, cycling stability, and viscoelastic properties. They also show the capacitor charging capabilities reaching their maximum charging points within 60 s.

Highly flexible mechanical energy harvester based on nylon 11 ferroelectric nanocomposites - Ram, Farsa; Radhakrishnan, Sithara; Ambone, Tushar; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2019)
We report here a flexible piezoelectric energy harvester using castor-oil-derived nylon 11 and biomass-derived cellulose nanocrystals (CNC). Using a simple solution casting process, we were able to fabricate flexible large area nylon 11 and composite films. Neat nylon 11 films crystallized predominantly in the α- phase. Incorporation of CNC at a low concentration of 2–5 wt % resulted in almost complete transition of α-phase to polar γ-phase, which could be attributed to strong hydrogen bonding interactions between CNC and amide groups in nylon 11. This remarkable shift in crystallization behavior also led to enhanced piezoelectric performance. We also found that the addition of 5 wt % glycerol (on the dry weight of nylon 11 or composite) enhanced the flexibility of the film. Energy harvesting devices made from 5 wt % nylon 11/CNC films showed about 2.6 times higher output voltage as compared to neat nylon 11 devices under similar impact conditions, and the effect was durable over 800 cycles. These devices were also used to charge a 10 μF polarized capacitor, and we found that the 5 wt % nylon 11/CNC devices charged up to 3.78 V in 90 s, which is 2.8 times higher than nylon 11 devices. To the best of our knowledge, this is the first report on nylon 11 nanocomposites, where cellulose nanocrystals have been used to enhance the electroactive γ phase in nylon 11 and yield such high piezoelectric performance.

Influence of nanocellulose on mechanics and morphology of polyvinyl alcohol xerogels - Pramanik, R.; Ganivada, B.; Ram, Farsa; Shanmuganathan, Kadhiravan; Arockiarajan, A. (Journal of the Mechanical Behavior of Biomedical Materials, 2019)
Xerogels are porous networks of crosslinked polymers that are useful for biomedical applications such as drug delivery, scaffold engineering, tissue regeneration, cell culture and wound dressing. However, inferior mechanical properties curtail their applications to a considerable extent. Nanocellulose fibers and crystals are often added into the polymer matrix to improve their mechanical strength. Here, nanocellulose in the mass ratios of 7%, 13% and 18% are loaded into polyvinyl alcohol (PVA) matrix followed by thermo-morpho-mechanical characterization. With increase in nanocellulose content, thermal degradation occurs at a lower temperature. It is observed that addition of higher quantity of nanocellulose crystals leads to the formation of weak cellulose rich regions causing xerogel rupture. This is predominantly observed for xerogel loaded with 18% nanocellulose crystals. Similarly, addition of higher quantity of nanocellulose fibers increase brittleness of the xerogels causing fracture. This is predominantly observed for xerogel loaded with 18% nanocellulose fibers. Creep strain and stress relaxation is observed to decrease with addition of nanocellulose loading owing to molecular chain restriction and polymer chain immobility.
Keywords: Mechanics; Morphology; Nanocellulose; Xerogels

Nanocellulose reinforced polymer composites as flexible mechanical energy harvesters - Shanmuganathan, Kadhiravan; Ram, Farsa (Abstracts of Papers of the American Chemical Society, 2019)

Enhancing thermomechanical and chemical stability of polymer electrolyte membranes using polydopamine coated nanocellulose - Ram, Farsa; Velayutham, Parthiban; Sahu, Akhila Kumar; Lele, Ashish K.; Shanmuganathan, Kadhiravan (ACS Applied Energy Materials, 2020)
We report here an approach to enhance the chemical and thermomechanical stability of polymer electrolyte membranes without compromising proton conductivity. Multifunctional polydopamine coated nanocellulose (PNC) was prepared by oxidative polymerization of dopamine on nano cellulose fibers and subsequently incorporated in Nafion by solution blending. PNC had a very significant effect on the thermomechanical properties of Nafion showing up to 200% improvement in the storage modulus at 90 degrees C. The PNC network also enhanced the dimensional stability of Nafion under constant stress. The 3 wt % PNC composite membrane showed a drastic reduction in creep compliance of about 39.9% and 46.5% in J(max) at 30 degrees and 60 degrees C, respectively. Free radical scavenging properties of polydopamine also helped to significantly enhance the chemical stability of Nafion, which was ascertained by accelerated degradation tests conducted in Fenton's reagent at 70 degrees C over 40 days. F-19 CP MAS solid state NMR, FTIR, and tensile tests on the membranes show higher chemical stability of the 3 wt % PNC composite membrane. The proton conductivity of the 3 wt % PNC composite membrane at 90 degrees C and 100% RH (similar to 125 mS/cm) was slightly higher than the Nafion membrane (similar to 94 mS/cm) at similar conditions. The retention of proton conductivity even with lower water uptake could be ascribed to proton hopping through polydopamine coated nanocellulose. Performance of the composite membrane was also evaluated in a single stack fuel cell and found to be better than recast Nafion. The benefits derived by this approach are not restricted to Nafion alone and shall broadly apply to many other polymer membranes.
Keywords: cellulose nanofibers; chemical stability; dimensional stability; fuel cell; polydopamine; polymer electrolyte membrane

Nanocellulose reinforced flexible composite nanogenerators with enhanced vibrational energy harvesting and sensing properties - Ram, Farsa; Gudadhe, Aniket; Vijayakanth, Thangavel; Aherrao, Swapnil; Borkar, Vivek; Boomishankar, Ramamoorthy; Shanmuganathan, Kadhiravan (2020)
We report here enhanced vibration and pressure sensing properties of nanocellulose reinforced flexible composite piezoelectric nanogenerators (PENGs). Surface fluorinated nanocellulose crystals (FNC) were incorporated into poly(vinylidene fluoride) (PVDF) and electrospun into composite nanofibers. Incorporation of only 2 wt % FNC in PVDF resulted in a significant enhancement in pressure sensitivity with a very low detectable pressure limit of 10 Pa and a sensitivity of up to 18 mV/kPa. The composite PENGs also demonstrated very high sensitivity for forced continuous vibrations. 2FNC/PVDF composites resulted in an order of magnitude higher voltage response over neat PVDF for a given strain. When PENGs were mounted on a vacuum pump for transduction of mechanical vibrations into electrical energy, 2FNC/PVDF composite devices manifested similar to 3.8 times enhanced voltage output over neat PVDF and faster charging of a capacitor. The enhanced piezoelectric properties of PVDF/FNC nanocomposites could be attributed to the tailored interface between PVDF and nanocellulose and enhanced polarizability.
Keywords: Composite; Nanofiber; piezoelectric; pressure; Sensor; vibration

Phosphorous-doped graphitic material as a solid acid catalyst for microwave-assisted synthesis of beta-ketoenamines and baeyer-villiger oxidation - Maity, Sayantan; Ram, Farsa; Dhar, Basab Bijayi (ACS Omega, 2020)
Synthesis of phosphorous-doped graphitic materials (P-Gc) using phytic acid as a precursor was done in a microwave oven in a cost- and time-effective green way. The material was used as a solid acid catalyst for microwave (MW)-assisted synthesis of beta-ketoenamines and Baeyer-Villiger (By) oxidation. In the case of BV oxidation, hydrogen peroxide (H2O2) was used as a green oxidant. For beta-ketoenamines, in most cases, 100% conversion with an similar to 95% yield was achieved in ethyl acetate medium. In solvent-free conditions, the yield of beta-ketoenamines was similar to 75%. A kinetic study suggested that the resonance stabilization of the positive reaction center happens in the transition state for beta-ketoenamine synthesis. In BV oxidation, cyclic ketones were converted to their corresponding cyclic esters in good to high yields (similar to 80% yield) in a shorter reaction time (6-20 min). As per our knowledge, this is the first report of BV oxidation catalyzed by a heteroatom-doped graphitic material. For BV oxidation, the phosphoric acid functional groups present in P-Gc might increase the electrophilicity of the carbonyl group of the ketones to compensate for the weakness of H2O2 as a nucleophile and a spiro-bisperoxide intermediate has been identified in high-resolution mass spectrometry.

Piezoelectric energy harvesting from a ferroelectric hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] embedded in a polymer matrix - Vijayakanth, Thangavel; Ram, Farsa; Praveenkumar, Balu; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2020)
Organic-inorganic hybrid ferroelectrics are an exciting class of molecular materials with promising applications in the area of energy and electronics. The synthesis, ferroelectric and piezoelectric energy harvesting behavior of a 3d metal ion-containing A(4)BX(6) type organic-inorganic hybrid salt [Ph3MeP](4)[Ni(NCS)(6)] (1) is now presented. P-E hysteresis loop studies on 1 show a remnant ferroelectric polarization value of 18.71 mu C cm(-2), at room temperature. Composite thermoplastic polyurethane (TPU) devices with 5, 10, 15 and 20 wt % compositions of 1 were prepared and employed for piezoelectric energy harvesting studies. A maximum output voltage of 19.29 V and a calculated power density value of 2.51 mW cm(-3) were observed for the 15 wt % 1-TPU device. The capacitor charging experiments on the 15 wt % 1-TPU composite device shows an excellent energy storage performance with the highest stored energies and measured charges of 198.8 mu J and 600 mu C, respectively.
Keywords: energy conversion; mechanical properties; non-covalent interactions; organic-inorganic hybrid composites; Phosphorus

PVDF/BaTiO3 films with nanocellulose impregnation: investigation of structural, morphological and mechanical properties - Ram, Farsa; Kaviraj, P.; Pramanik, R.; Krishnan, Amrutha; Shanmuganathan, Kadhiravan; Arockiarajan, A. (Journal of Alloys and Compounds, 2020)
Polyvinylidene fluoride (PVDF) composite films have witnessed widespread applications in biomedical and flexible electronic devices in recent years. These applications require a material that has enhanced electrical properties, mechanical flexibility along with sufficient strength. A lot of research has been carried out to enhance the piezoelectric and dielectric properties of the PVDF composite films. However, the improvements in the mechanical properties of nano filler reinforced PVDF composite films has not received due attention. In this regard, the present work focuses towards enhancing the mechanical strength and load-bearing capability of PVDF, by preparing composites of PVDF films impregnated with Cellulose Nanocrystals (CNC) and Barium Titanate (BTO) nanoparticles. Solution casting method was adapted to fabricate the PVDF/BTO/CNC films. X-ray diffractograms and FTIR (Fourier Transform infrared spectroscopy) corroborate the presence of ferroelectric gamma phase in PVDF. Mechanical and viscoelastic measurements have been carried out to examine the influence of CNC and BTO nano fillers in the PVDF matrix. The addition of CNC and BTO in PVDF film has improved the mechanical strength significantly. The stress achieved for PVDF/5% BTO and PVDF/5% BTO with 0.9% of CNC at 5% strain was 17% and 130% higher than the pristine PVDF, respectively. This study can be helpful for the design engineers to meet custom/specific requirements for a myriad of end- user applications such as piezoelectric nanogenerators. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: BaTiO3; Composite films; Mechanics; Morphology; Nanocellulose; PVDF

Elastic piezoelectric aerogels from isotropic and directionally ice-templated cellulose nanocrystals: comparison of structure and energy harvesting - Ram, Farsa; Biswas, Bipul; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Cellulose, 2021)
We report the preparation of highly compressible and elastic piezoelectric aerogels of carboxylated cellulose nanocrystals (CNCs). Aqueous CNC dispersions containing polyethyleneimine and crosslinker were frozen isotropically to yield isotropic aerogels, while oriented aerogels were prepared by directional freezing. These aerogels were highly flexible and porous (similar to 85% void fraction), exhibiting greater than 90% recovery at 50% compressive strain even after 100 compression-decompression cycles. Since such aerogels with low bulk modulus and high anisotropy would be an ideal platform for leveraging the piezoelectric properties of CNCs, we used them to prepare piezoelectric nanogenerator devices and determined their energy transduction behavior. Anisotropic aerogels led to an enhanced open-circuit voltage of 840 mV (at similar to 8 N applied force), which is over 2.6 times higher than isotropic aerogels (320 mV). The energy density of anisotropic aerogels was around 52 nW/cm(2), representing outstanding piezoelectric performance for cellulose-based aerogels. Such aerogels with high compressibility, elastic recovery and exceptional piezoelectric performance could have potential applications in sensors, wearable electronics, etc.
Keywords: Aerogel; Anisotropic; Cellulose nanocrystals; energy harvesting; Piezoelectricity

Highly compressible ceramic/polymer aerogel-based piezoelectric nanogenerators with enhanced mechanical energy harvesting property - Ram, Farsa; Suresh, Karthika; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Ceramics International, 2021)
Ceramic piezoelectric materials have orders of magnitude higher piezoelectric coefficients compared to polymers. However, their brittleness precludes imposition of large strains in mechanical energy harvesting applications. We report here that ice templating affords low bulk modulus lead-free aerogel piezoelectric nanogenerators (PENG) with unprecedented combination of flexibility and high piezoelectric response (voltage and power density). A modified ice templating protocol was used to fabricate piezoelectric nanocomposites of surface modified BaTiO3 (BTO) nanoparticles in crosslinked polyethylene imine. This protocol allowed incorporating a significantly high fraction of BTO particles (up to 83 wt %) in the aerogel, while retaining remarkably high compressibility and elastic recovery up to 80% strain. The output voltage, at an applied compressive force of 20 N (100 kPa), increased with BTO loading and a maximum output voltage of 11.6 V and power density of 7.22 ?W/cm2 (49.79 ?W/cm3) was obtained for PENG aerogels containing 83 wt% BTO, which is orders of magnitude higher than previously reported values for foam-based piezoelectric energy harvesters. The BTO/PEI PENGs also showed cyclic stability over 900 cycles of deformation. PENGs with higher porosity showed better elastic recovery and piezoelectric properties than lower porosity and higher BTO content aerogels. To the best of our knowledge, this is the first report to demonstrate the piezoelectric properties of high ceramic content aerogels having very high compressibility and elastic recovery.
Keywords: Ceramic polymer aerogels; energy harvesting; ice templating; piezoelectric

CdS cubane type clusters encapsulated by rolling of single layer reduced graphene oxide sheets for enhanced mechanical energy harvesting - Kumar, Praveen; Ram, Farsa; Shanmuganathan, Kadhiravan; Luwang, Meitram Niraj (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Composites with Single Layer Graphene Oxide (SLGO) sheets are extremely difficult to achieve, irrespective of the current advancements in graphene composites research. The difficulties in exfoliating the graphite oxide (GO) was associated with a strong interaction among the edge sides of the adjacent layers. This in-turn barricades the foreign intruders to interact with the basal plane, thereby restraining one to form composites with SLGO sheets. In this work, we had successfully exfoliated GO through a spacer [Cd(OAc)(2) + polyethylene glycol (PEG)] to result in nano-engineered CdS cubane-type clusters in rolled up SLGO to form graphene oxide complex compound (GOCC), resembling carbon nanotubes (CNTs). The CdS cubane-type clusters were found to interacting with the carbon skeleton of rolled reduced SLGO sheet through a Manogate' structures, which was supported by density functional theory (DFT) calculations. Our theoretical study reveals that the obtained complex compound (GOCC) is thermodynamically more favourable than its ancestor materials (CdS cubane and empty CNT). Flexible piezoelectric nanogenerators (PENGs) fabricated from GOCC and thermoplastic polyurethane (TPU) resulted in output voltage (V-oc) of 4.5 V and output current of 0.4 mu A at applied force of 13 N. The nanoengineering helps to achieve superior mechanical energy harvesting performance for GOCC compared to pristine CdS, which demonstrate the potential of nanogate structures to enhance the intrinsic properties of materials.
Keywords: Graphene oxide complex compound; Nanogate structure; New material; Novel procedure; Piezoelectric nanogenerator; SLGO

Nanocellulose/melanin-based composites for energy, environment, and biological applications - Ram, Farsa; Yadav, Prashant; Shanmuganathan, Kadhiravan (Journal of Materials Science, 2022)
Melanins, a class of brown-black pigments present in many natural sources, exhibit unique physical and chemical properties such as photoprotection, photoconductivity, metal ion chelation, free radical quenching, proton conductivity, and significant antimicrobial properties. These properties could be leveraged in various environmental and energy applications. However, their limited solubility makes them less amenable to processing. Over the last decade, there has been tremendous interest in developing synthetic analogs of melanin that are easy to dissolve and process. Nonetheless, melanins or their synthetic analogs cannot form mechanically robust free-standing films and fibers. This drawback could be partly circumvented by creating composites of melanin with nanocellulose, a nanomaterial derived from cellulosic biomass. Composites of melanins and nanocellulose offer an opportunity to utilize the functional aspects of melanin-like polymers in a mechanically stable nanocellulose network. This review attempts to capture the recent developments on this topic with special emphasis on technologically relevant applications.